Relevance of the SDGs to Corporate Social Responsibility: The Case of 20 Colombian Companies - Bohórquez Camacho, Silvia Ivanna; Hoyos Contreras, Sergio Alexander; Camargo Morales, Fabio (Ingeniería Solidaria, 2026)
Introduction: This article stems from the social outreach project “Corporate Social Responsibility” (CSR), affiliated with the Vice-Rector’s Office of Outreach and Welfare at the University of Pamplona. As a founding member of the United Nations, Colombia is committed to the 2030 Agenda and the Sustainable Development Goals (SDGs). This research analyzes the role of the SDGs within the CSR agenda of 20 large Colombian companies across four economic sectors. Objective: To analyze the role of the SDGs within CSR agendas in the Colombian context, determine their relevance, identify which goals receive greater attention, and assess the impact of corporate efforts in achieving them. Methodology: A mixed-methods approach was employed, combining both quantitative and qualitative techniques. Sustainability reports from 20 companies selected through convenience sampling were analyzed, and interviews were conducted with six sustainability leaders and two communications leaders. Results: Companies are responding to the global call to contribute to sustainable development, with a focus on SDGs 8, 9, 13, and 16. While there is a positive trend toward incorporating SDGs into CSR strategies, there is also a noticeable concentration on specific goals. Conclusion: CSR strategies in Colombia show strong alignment with the SDGs. Companies demonstrate their commitment through concrete actions and initiatives that reflect the global development agenda. Originality: This study addresses a gap in the literature by exploring how Colombian companies integrate SDGs into their CSR strategies and how they communicate their efforts to stakeholders. Limitations: Challenges in contacting sustainability and communications leaders, limited availability for interviews, and restricted direct access to companies affect the representativeness and generalizability of the findings.